2009
DOI: 10.1073/pnas.0908286106
|View full text |Cite
|
Sign up to set email alerts
|

High resilience in the Yamal-Nenets social–ecological system, West Siberian Arctic, Russia

Abstract: Tundra ecosystems are vulnerable to hydrocarbon development, in part because small-scale, low-intensity disturbances can affect vegetation, permafrost soils, and wildlife out of proportion to their spatial extent. Scaling up to include human residents, tightly integrated arctic social-ecological systems (SESs) are believed similarly susceptible to industrial impacts and climate change. In contrast to northern Alaska and Canada, most terrestrial and aquatic components of West Siberian oil and gas fields are sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
195
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(205 citation statements)
references
References 40 publications
3
195
0
1
Order By: Relevance
“…In fact, Inuit philosophies about the future, long-term planning and predictions challenge the basic premise of Western scientific approaches to climate change adaptation: that long-term forecasting is essential to effective decision-making. It is instructive to note that several studies have suggested that indigenous people in the Arctic indeed have the necessary knowledge and skills to adapt to climate change (Berkes and Joly, 2001;Forbes et al, 2009). In short, the Inuit/Western science example illustrates the fundamental challenges of 'integrating' knowledge among different ontological traditions and communities (Bates, 2007).…”
Section: Illustrative Casementioning
confidence: 99%
“…In fact, Inuit philosophies about the future, long-term planning and predictions challenge the basic premise of Western scientific approaches to climate change adaptation: that long-term forecasting is essential to effective decision-making. It is instructive to note that several studies have suggested that indigenous people in the Arctic indeed have the necessary knowledge and skills to adapt to climate change (Berkes and Joly, 2001;Forbes et al, 2009). In short, the Inuit/Western science example illustrates the fundamental challenges of 'integrating' knowledge among different ontological traditions and communities (Bates, 2007).…”
Section: Illustrative Casementioning
confidence: 99%
“…Images from Landsat satellites are used at regional or landscape scale to study any changes (NASA, 2007). These changes may be vegetation dynamics by Normalized Difference Vegetation Index (NDVI), hydrology, permafrost, dynamics, and land-use by wildlife and humans (Forbes et al, 2009;Myers-Smith et al, 2011).…”
Section: Data Acquisitionmentioning
confidence: 99%
“…[48]) and are expected to become more frequent [49]. Tactics for adaptive management of caribou and reindeer as subsistence resources in a rapidly changing Arctic include monitoring and surveillance of current and future pests [50,51] and application of local ecological knowledge [52] of animal movements in response to food availability and pest abundance [53].…”
Section: (C) Ecosystem Consequencesmentioning
confidence: 99%